1981
DOI: 10.1161/01.cir.63.4.793
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and angiographic predictors of operative mortality from the collaborative study in coronary artery surgery (CASS).

Abstract: SUMMARY Fifteen institutions participating in the Collaborative Study in Coronary Artery Surgery (CASS) have performed isolated coronary artery bypass surgery upon 6630 patients (1061 women and 5569 men) for coronary artery disease. The overall operative mortality (OM) was 2.3% (range 0.3-6.4%). Mortality increased with age, from 0 in the group 20-29 years old to 7.9% In the group 70 years and older. OM was higher for women in each age group, ranging from 2.8% for ages 30-39 years to 12.3% for age 70 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
11

Year Published

1981
1981
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(113 citation statements)
references
References 34 publications
(4 reference statements)
4
98
0
11
Order By: Relevance
“…Estimates for ages [45][46][47][48][49][50][51][52][53][54] were based on an average of the Minnesota data for 1970 and 1980, adjusted for first MI. The sex-specific case fatality rates for ages [35][36][37][38][39][40][41][42][43][44] were assumed to be equal to the adjusted Minnesota rates for ages 45- persons routinely referred for CABG may be at greater risk than their medically treated counterparts, in contrast to randomized trials in which the patients in both groups are drawn from the same population. The probability that a cardiac arrest will be accompanied by MI in a given year was estimated as in the Bridge Model.…”
Section: Resiultsmentioning
confidence: 99%
“…Estimates for ages [45][46][47][48][49][50][51][52][53][54] were based on an average of the Minnesota data for 1970 and 1980, adjusted for first MI. The sex-specific case fatality rates for ages [35][36][37][38][39][40][41][42][43][44] were assumed to be equal to the adjusted Minnesota rates for ages 45- persons routinely referred for CABG may be at greater risk than their medically treated counterparts, in contrast to randomized trials in which the patients in both groups are drawn from the same population. The probability that a cardiac arrest will be accompanied by MI in a given year was estimated as in the Bridge Model.…”
Section: Resiultsmentioning
confidence: 99%
“…Estes fatores são necessariamente restritos aos resultados pré-operatórios e não podem incluir parâme-tros peri e pós-operatórios 25 . Baseando-se na definição descrita, a partir de 1980 teve início o desenvolvimento de escalas de risco que visavam sobretudo a avaliação da mortalidade operatória 10,[26][27][28][29][30] . Dentre os parâmetros mais comuns para análise do pré-operatório, encontram-se a idade [31][32][33][34][35][36] , o sexo 11,37-40 , a função do VE [41][42][43][44] , as doenças co-mórbidas 45,46 , a angiografia coronária com aterosclerose proximal ou distal 47,48 .…”
Section: Pré-operatóriounclassified
“…Observational studies have shown that patients with LV dysfunction who are undergoing CABG have a higher perioperative and long-term mortality than patients with normal LV function (15)(16)(17)(18). The presence of comorbid conditions also contributes significantly to higher perioperative mortality.…”
Section: The Role Of Cabgmentioning
confidence: 99%